Experimentation of Advance Organizer Learning on Students' Cognitive Abilities - Suhendar (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2020)
Learning outcomes, especially cognitive abilities of students are generally still low with a variety of learning models in schools that are still limited. Various models and learning approaches have been tried but the results have not been satisfactory. This study aims to obtain information about the effect of applying the Advance Organizer learning model to the learning outcomes of high school students. This type of research is quasi-experimental with pre-test post-test control group design. The population in this study were high school class X students with a sample of 2 classes. Sampling using a purposive sampling technique. Research instruments in the form of cognitive test questions refer to the revised Bloom's taxonomy. T test results at a significance level of 0.05, indicating that t = 2.56 is greater than t table = 1.99 so that H0 is rejected and H1 is accepted, meaning that there are significant differences in cognitive abilities in the experimental class and the control class. Based on the analysis of differences in the average score of learning outcomes shows that the application of the Advance Organizer learning model has a significant effect on student learning outcomes at each indicator and at every cognitive level.